2017
DOI: 10.1002/mus.25561
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity distribution simulations of surface electrode configurations for electrical impedance myography

Abstract: OBJECTIVE Surface-based electrical impedance myography (EIM) is sensitive to muscle condition in neuromuscular disorders. However, the specific contribution of muscle to the obtained EIM values is unknown. METHODS We combined theory and the finite element method to calculate the electrical current distribution in a three-dimensional model using different electrode array designs and subcutaneous fat thicknesses (SFT). Through a sensitivity analysis, we decoupled the contribution of muscle from other surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…For the placement of the electrodes, we had to consider that in deep injuries (near the bone), the current electrodes should be placed with a greater separation than in superficial injuries to increase the depth of the current's penetration. These considerations are in agreement with those reported by Sanchez et al (2016) and more recently by Rutkove et al (2017). The positioning of the electrodes for L-BIA is crucial in correctly assessing muscle injury and following recovery until the RTP because inconsistent electrode positioning can influence the measurement.…”
Section: L-biasupporting
confidence: 90%
“…For the placement of the electrodes, we had to consider that in deep injuries (near the bone), the current electrodes should be placed with a greater separation than in superficial injuries to increase the depth of the current's penetration. These considerations are in agreement with those reported by Sanchez et al (2016) and more recently by Rutkove et al (2017). The positioning of the electrodes for L-BIA is crucial in correctly assessing muscle injury and following recovery until the RTP because inconsistent electrode positioning can influence the measurement.…”
Section: L-biasupporting
confidence: 90%
“…In injuries located near the bone detector, voltage electrodes were placed 10 cm proximally and 10 cm distally, respectively, from the center of the injury to increase the sensitivity of the measurement (Sanchez et al, 2016;Rutkove et al, 2017).…”
Section: Localized Bioimpedance Measurements (L-bia)mentioning
confidence: 99%
“…In a previous study [7] it was suggested that proper electrode configuration can reduce the influence of subcutaneous fat thickness, muscle size, and conductivity on EIM impedance value. In another study [8] it was found that the contribution of muscle layer to surface EIM value varies greatly depending on electrode configurations and fat thickness values. However, the existing research is limited to the surface EIM (sEIM) [9], whose impedance value is derived from the contribution of countless tiny areas, such as fat, skin, and bone.…”
Section: Introductionmentioning
confidence: 97%
“…However, the existing research is limited to the surface EIM (sEIM) [9], whose impedance value is derived from the contribution of countless tiny areas, such as fat, skin, and bone. Therefore, scientists have introduced finite element modeling (FEM) or finite difference time domain method (FTDT) to perform a "sensitivity" analysis on human tissues or organs to determine the impedance values of all conductive tissues inside to select the optimal configuration mode of surface electrodes to improve the selectivity and sensitivity to the target area [10]. Seward Rutkove introduce model component analysis (MCA)to separate the impedivity of subcutaneous fat and muscle tissues from sEIM data [11].…”
Section: Introductionmentioning
confidence: 99%